Determinants of nutritional status among children under age 5 in Ethiopia: further analysis of the 2016 Ethiopia demographic and health survey - Zerihun Yohannes Amare; Mossa Endris Ahmed; Adey Belete Mehari (BMC, 2019)
Abstract Background The aim of this study was to examine the determinants of nutritional status among children under age 5 (0-59 months) in Ethiopia. Child malnutrition is an underlying cause of almost half (45%) of child deaths, particularly in low socioeconomic communities of developing countries. In Ethiopia, the prevalence of stunting decreased from 47% in 2005 to 39% in 2016, but the prevalence of wasting changed little over the same time period (from 11 to 10%). Despite improvements in reducing the prevalence of malnutrition, the current rate of progress is not fast enough to reach the World Health Organization global target for reducing malnutrition 40% by 2025. Methods This study used data from the 2016 Ethiopia Demographic and Heath Survey (EDHS). The analysis used stunting and wasting as dependent variables, while the independent variables were characteristics of children, mothers, and households. Logistic regression was used to analyze the determinants of nutritional status among children. Bivariate analysis was also used to analyze the association between the dependent and independent variables. Results Study results show that child's age, sex, and perceived birth weight, mother's educational status, body mass index (BMI), and maternal stature, region, wealth quintile, type of toilet facility, and type of cooking fuel had significant associations with stunting. Child's age, sex, and perceived birth weight, mother's BMI, and residence and region showed significant associations with wasting. The study found that child, maternal, and household characteristics were significantly associated with stunting and wasting among children under age 5. Conclusion These findings imply that a multi-sectorial and multidimensional approach is important to address malnutrition in Ethiopia. The education sector should promote reduction of cultural and gender barriers that contribute to childhood malnutrition. The health sector should encourage positive behaviors toward childcare and infant feeding practices. More should be done to help households adopt improved types of toilet facilities and modern types of cooking fuels.